Hepcidin regulates ferroportin expression and intracellular iron homeostasis of erythroblasts - Zhang, De-Liang (American Society of Hematology, 2011)
The iron-regulatory hormone, hepcidin, regulates systemic iron homeostasis by interacting with the iron export protein ferroportin (FPN1) to adjust iron absorption in enterocytes, iron recycling through reticuloendothelial macrophages, and iron release from storage in hepatocytes. We previously demonstrated that FPN1 was highly expressed in erythroblasts, a cell type that consumes most of the serum iron for use in hemoglobin synthesis. Herein, we have demonstrated that FPN1 localizes to the plasma membrane of erythroblasts, and hepcidin treatment leads to decreased expression of FPN1 and a subsequent increase in intracellular iron concentrations in both erythroblast cell lines and primary erythroblasts. Moreover, injection of exogenous hepcidin decreased FPN1 expression in BM erythroblasts in vivo, whereas iron depletion and associated hepcidin reduction led to increased FPN1 expression in erythroblasts. Taken together, hepcidin decreased FPN1 expression and increased intracellular iron availability of erythroblasts. We hypothesize that FPN1 expression in erythroblasts allows fine-tuning of systemic iron utilization to ensure that erythropoiesis is partially suppressed when nonerythropoietic tissues risk developing iron deficiency. Our results may explain why iron deficiency anemia is the most pronounced early manifestation of mammalian iron deficiency.